2021
DOI: 10.3390/polym13234083
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dynamic Mechanical Properties of the Amino Silicone Oil Emulsion Modified Ramie Fiber Reinforced Composites

Abstract: The mechanical and dynamic mechanical properties, interface adhesion and microstructures of the amino silicone oil emulsion (ASO) modified short ramie fiber reinforced polypropylene composites (RFPCs) with different fiber fractions were investigated. The RFPCs were made through a combined process of extrusion and injection molding. Mechanical property tests of the RFPCs revealed enhancements in tensile and flexural strengths with increase of the fiber fraction due to the high stiffness of the fiber filler and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…The results are in line with prior research that found decreased E-factor of various reinforced polymer composites. Incorporating increased wood waste fibers into poly(3-hydroxybutyrate) by Panaitescu et al [ 68 ], graphite flake into acrylonitrile butadiene styrene by Pandey et al [ 69 ], carbon nanotubes into poly(ether ketone) by Chauhan et al [ 70 ], and ramie fiber into polypropylene by He et al [ 71 ] has been shown to decrease the E-factor of the resulting composites.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The results are in line with prior research that found decreased E-factor of various reinforced polymer composites. Incorporating increased wood waste fibers into poly(3-hydroxybutyrate) by Panaitescu et al [ 68 ], graphite flake into acrylonitrile butadiene styrene by Pandey et al [ 69 ], carbon nanotubes into poly(ether ketone) by Chauhan et al [ 70 ], and ramie fiber into polypropylene by He et al [ 71 ] has been shown to decrease the E-factor of the resulting composites.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…An impulse hammer excitation [ 16 ] test is performed on the fabricated samples in accordance with the recommendations outlined in ASTM E756 [ 25 ]. A free vibration test is performed to find the natural frequency and damping factors.…”
Section: Methodsmentioning
confidence: 99%
“…Benazir et al [ 15 ] studied the properties of Cyperus pangorei rottb. The addition of ramie fibers in a composite gives a good vibration damping effect [ 16 ]. At present, the void content of the composites has been successfully studied using a CT scan, which is a non-destructive method [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the Cole-Cole plots are commonly used to analyze experimental data and inspect theoretical models. In [39], dynamic properties of a sort of polypropylene composites were investigated based on the Cole-Cole plot analysis. In [40], Cole-Cole plots were used to analyze the viscoelastic and mechanical properties of smart thermoplastic elastomeric materials based on recycled rubber shred.…”
Section: The Response Function and The Complex Dielectric Permittivitymentioning
confidence: 99%